1990
DOI: 10.3109/08977199009037499
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Functional Basic Fibroblast Growth Factor Receptors on the Surface of BHK and NIH 3T3 Cells

Abstract: The recovery of functional cell-surface bFGF receptors after trypsin treatment was studied in BHK cells and NIH 3T3 cells. Restoration of functional bFGF receptors occurred at an approximately linear rate with 50% of the high-affinity binding capacity restored after 4 hr. Restoration of functional receptors required protein synthesis but not RNA synthesis. Upon exposure of BHK cells to bFGF, cell-surface receptors were rapidly lost, with only 25% remaining after 1 hr. When the bFGF was removed, down-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…This is consistent with previous data demonstrating that FGFRs were constantly turning over in the presence or in the absence of ligand (38). In contrast, we showed that FGFR1 was more rapidly and to a greater extent activated by secreted FGF1 in aged RPE cells than in early passage RPE cells.…”
Section: Erk2 Activation and Synthesis In Aged Rpe Cellssupporting
confidence: 93%
“…This is consistent with previous data demonstrating that FGFRs were constantly turning over in the presence or in the absence of ligand (38). In contrast, we showed that FGFR1 was more rapidly and to a greater extent activated by secreted FGF1 in aged RPE cells than in early passage RPE cells.…”
Section: Erk2 Activation and Synthesis In Aged Rpe Cellssupporting
confidence: 93%
“…Rather, a most striking phenomenon was the transient disappearance of FGFR2 in FGF2-stimulated cells, unveiling an inhibitory feedback controlling FGF2-dependent signaling in astrocytes. A comparable phenomenon has been reported in NIH 3T3 cell lines [53] , wherein FGFR internalization followed by degradation leads to receptor desensitization. It appears overall that a cell membrane rather than a nuclear FGFR2 accounts for the immunomodulatory actions of LMW-FGF2 in cerebellar astrocytes.…”
Section: Discussionmentioning
confidence: 59%
“…The kinetics of bFGF in the pericellular environment may involve repeated binding and release both from the bFGF tyrosine kinase receptor and from heparan sulfate proteoglycan on the cell surface and within the extracellular matrix (35)(36)(37)(38). This mechanism has been postulated as a means of maintaining multiple molecules of bFGF within a small domain of binding sites (38).…”
Section: Discussionmentioning
confidence: 99%